Pharmacokinetics of cannabidiol, (-)-trans-Δ9-tetrahydrocannabinol, and their oxidative metabolites after intravenous and oral administration of a cannabidiol-dominant full-spectrum hemp product to beagle dogs - Kitts-Morgan, Susanna E.; Sams, Richard A.; Muir, William W. (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigated the pharmacokinetics, safety, and tolerability of a full-spectrum CBD-dominant oil formulated in medium-chain triglycerides (MCT oil) after a single intravenous (IV) administration, a single oral (PO) administration, and multiple oral administrations of CBD at a dose of 2.2 mg/kg in adult male and female beagle dogs.MethodsThe CBD-dominant extract was administered to adult, intact beagle dogs (male n = 4, female n = 2) once intravenously, once orally, and every 12 h orally for 21 days at a dose of 2.2 mg CBD/kg body weight (BW). Blood samples were collected at predetermined times to measure concentrations of serum CBD, 7-hydroxy-CBD (7-OH-CBD), 7-nor-7-carboxy-CBD (7-COOH-CBD), Δ9-tetrahydrocannabinol (Δ9-THC), 11-hydroxy-THC (11-OH-THC), and 11-carboxy-THC (11-COOH-THC). Serum CBD and Δ9-THC concentrations were analyzed to estimate various pharmacokinetic parameters. Selected physical, behavioral, hematologic, and blood chemical measurements were obtained before and during single and repeated dose administrations.ResultsPharmacokinetics of CBD after IV administration indicated a median (range) systemic clearance (CL) of 7.06 (6.14–10.5) mL/min/kg, a steady-state volume of distribution (Vss) of 2.13 (1.10–2.85) L/kg, and a half-life of 291 (183–508) min. The median (range) extent of systemic availability of CBD after a single oral dose was 31.2 (17.7–35.7)%. Pharmacokinetics of Δ9-THC after IV administration were characterized by a CL of 8.85 (6.88–14.4) mL/min/kg, Vss of 1.98 (1.30–2.30) L/kg, and a half-life of 169 (139–476) min. The extent of systemic availability of Δ9-THC after PO administration was 40.9 (20.5–46.2)%. The test article was well tolerated in all dogs during the study. Although serum alkaline phosphatase concentrations increased during the repeated PO dose study, they remained within normal limits.DiscussionBoth CBD and Δ9-THC were rapidly cleared after IV administration and exhibited extensive volumes of distribution. Comparison of clearance to serum hepatic blood flow estimated the hepatic extraction ratio and extent of first pass metabolism after PO administration, which was confirmed by analyzing the single PO dose pharmacokinetic data. The AUC0−∞ for 7-OH-CBD after single IV compared to single PO dose was not different, suggesting complete absorption of CBD from the formulation in MCT oil when administered with canned dog food.